Composition of supervisory boards in Germany: Inside or outside control of banks? - Ettore Andreani; Kathrin Dummann; Doris Neuberger (Universität Rostock, Institut für Volkswirtschaftslehre, 2009)
This paper examines the composition of supervisory boards of German banks for a sample of 41 large banks in the period 1999-2006. We find that the supervisory board structure reflects both outside control by shareholders and inside control by stakeholders. Most of the non-employee board members are representatives of other banks and industrial companies. The high presence of former executives and German board members indicates inside control. In banks controlled by other banks or insurance companies it is less likely that the chairperson of the supervisory board is a former executive of the same bank. Over time, inside networking through the supervisory board decreased.
Keywords: G21; G34; 330; corporate governance; dual board system; principal agent theory; stakeholder theory; banks; Bank; Aufsichtsrat; Eigentümerstruktur; Soziales Netzwerk; Corporate Governance; Stakeholder